(untitled) (Bangladesh Medical Journal Khulna, 2012)
This was an observational study carried out among all cancer patients attended at radiotherapy department of Khulna medical college hospital between January 2010 and December 2010. The study aimed to develop a primary data source for further research and improvement of patient care. Data were collected by a questionnaire. Total study population was 321 and out of them 158 was male and 163 were female. Top five organs involved with malignancies of both sexes are breast (14.64%), non-Hodgkins Lymphoma (1 0.59%), lung (7.79%), mouth and oral cavity (7.48%), and stomach (7.48%). This hospital-based cancer registry should be maintained to improve the treatment facilities and follow-up system. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10471 Bang Med J (Khulna) 2011: 44(1&2) 18-24